Psychosocial characteristics of students with learning disabilities - Ališauskas, Algirdas; Galvydytė, Jelena (Special Education, 2017)
The article describes the psychosocial characteristics of students with learning disabilities. Qualitative data collection and processing (interview and interview content analysis) and quantitative (socio-metric research) methods have been applied. Positive and negative psychosocial (emotional self-satisfaction/feeling, self-actualisation and self-expression and inter- personal relations) characteristics of a student with learning disabilities have been distinguished and defined. The social status of these students has been ascertained within the class and the motives of the classmates in their choices have been revealed. A psychosocial portrait (according to feeling well, self- actualisation, and the quality of interpersonal relationship) of a student with learning disabilities is ambiguous, reconciling both positive and negative characteristics. In the class, a relatively high status of students with learning disabilities has been identified. Positive and negative classmate’s choices mostly related to personal qualities and acceptable or unacceptable behaviour of the students with learning disabilities. An analysis of interview content revealed the factors determining self-esteem, self-expression, and interpersonal relationships of students with learning disabilities.